Digital Echoes: Crafting Chinese EFL Teacher Identity in the Era of AI-Enhanced Instruction—A Qualitative Exploration - Zhou, Qing; Hashim, Harwati; Sulaiman, Nur Ainil (Forum for Linguistic Studies, 2024)
This study examines the impact of artificial intelligence (AI) integration on the professional identities of Chinese tertiary English as a Foreign Language (EFL) teachers. It explores how these educators perceive and adapt to the incorporation of AI tools into their teaching practices, focusing on both the opportunities and challenges encountered. Through qualitative analysis of semi-structured interviews with 16 tertiary EFL teachers, the study identifies key factors influencing their professional identities, including institutional support, professional development, peer influence, personal attitudes towards technology, and ethical considerations. The findings indicate that AI integration enhances personalized learning and reduces the burden of administrative tasks. However, it also challenges teachers to reshape their roles and manage both technological and ethical complexities effectively. The study highlights the necessity for ongoing professional development and robust institutional support to effectively integrate AI in educational settings, ensuring it enhances rather than undermines the teaching and learning process.